A Comparative Study on Current- and Voltage-Optimized Circuit Scheme for Multiple-Transmitter and Single-Receiver WPT System. (13th August 2020) - Zhang, Jin; Xu, Weiao; Chen, Dong; Zhang, Chen
Abstract : As an important structural system for effectively improving power delivered to the load (PDL) and power transmission range, multiple-transmitter (TX) and single-receiver (RX) wireless power transfer (WPT) system is gaining more and more attention in both academic circles and the industrial fields. Based on the Lagrange multiplier method, this paper first provides a current- and voltage-optimized circuit scheme to maximize the PDL of the multiple-TX WPT system. Then, for a determined WPT system, the current-optimized circuit scheme is proposed to maximize the PDL effectively with constant source voltages and feeding currents for TXs. While voltage-optimized circuit scheme can effectively adjust the source voltages and feeding currents and maintain the same level of input power and PDL as a current-optimized solution. Through comparative study, the voltage-optimized solution shows its advantages in adjustable source voltage and feeding current without any degradation of PDL. Finally, the theoretical analysis results are confirmed by the results of full-wave electromagnetic simulation.